2016
DOI: 10.1038/srep21982
|View full text |Cite
|
Sign up to set email alerts
|

BPA-Induced Deregulation Of Epigenetic Patterns: Effects On Female Zebrafish Reproduction

Abstract: Bisphenol A (BPA) is one of the commonest Endocrine Disruptor Compounds worldwide. It interferes with vertebrate reproduction, possibly by inducing deregulation of epigenetic mechanisms. To determine its effects on female reproductive physiology and investigate whether changes in the expression levels of genes related to reproduction are caused by histone modifications, BPA concentrations consistent with environmental exposure were administered to zebrafish for three weeks. Effects on oocyte growth and maturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 43 publications
9
64
0
Order By: Relevance
“…It is also present in the environment as a result of manufacturing processes and leaching from the products in which it is used. BPA is defined as an endocrine disruptor because of its ability to elicit both proestrogenic and antiestrogenic effects by binding to estrogen receptors ERα and ERβ and altering transcription in tissue- and context-specific manners (Santangeli et al, 2016). BPA binds to the zebrafish estrogen-related receptor gamma (ERRγ) in vivo (Tohmé et al, 2014).…”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…It is also present in the environment as a result of manufacturing processes and leaching from the products in which it is used. BPA is defined as an endocrine disruptor because of its ability to elicit both proestrogenic and antiestrogenic effects by binding to estrogen receptors ERα and ERβ and altering transcription in tissue- and context-specific manners (Santangeli et al, 2016). BPA binds to the zebrafish estrogen-related receptor gamma (ERRγ) in vivo (Tohmé et al, 2014).…”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%
“…Interestingly, this pathway is independent of signaling through the estrogen receptor (Fitzgerald et al, 2015). BPA is suggested to act through epigenetic mechanisms through histone modification and alteration of DNA methylation (Faulk et al, 2016; Kundakovic & Champagne, 2011; Santangeli et al, 2016), and zebrafish studies have provided key mechanistic insights. The effect of BPA on histone methylation patterns and DNA methylation has recently been shown in adult zebrafish (Laing et al, 2016; Santangeli et al, 2016).…”
Section: Pathways and Mechanisms Of Toxicant-induced Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, estrogen receptor β (ER- β ) and aryl hydrocarbon receptor-mediated pathways have been implicated in fetal meiosis and adult follicle growth, respectively (31, 37). Importantly, experimental data suggest that BPA exposure also interferes with the epigenetic reprogramming of the female germline that occurs during follicle growth (38, 46) and in the early preimplantation embryo ([47] and reviewed in Eichenlaub-Ritter and Pacchierotti [48]). Although direct links between BPA, receptor signaling, and epigenetic modifications in the oocyte have not yet been delineated, the role of the epigenome in fetal development and adult disease makes this is a critical area of investigation.…”
Section: The Ovary: Vulnerability At Multiple Stagesmentioning
confidence: 99%
“…Activation of this pathway prevents the resumption of meiotic maturation in ish oocytes [83]. Study showed that BPA downregulated oocyte maturation-promoting signals through changes in the chromatin structure mediated by histone modiications in zebraish [85].…”
Section: Bisphenol a Exposure And Health Risksmentioning
confidence: 99%